Filarial nematode phenotypic screening cascade to identify compounds with anti-parasitic activity for drug discovery optimization. (August 2022) - Hawryluk, Natalie; Zhiru, Li; Carlow, Clotilde; Gokool, Suzanne; Townson, Simon; Kreiss, Tamara; Chojnowski, Agnieszka; Prorok, Monika; Siekierka, John; Ehrens, Alexandra; Koschel, Marianne; Lhermitte-Vallarino, Nathaly; et al.
Abstract: Filarial diseases, including lymphatic filariasis and onchocerciasis, are considered among the most devastating of all tropical diseases, affecting over 86 million people worldwide. To control and more rapidly eliminate onchocerciasis requires treatments that target the adult stage of the parasite. Drug discovery efforts are challenged by the lack of preclinical animal models using the human-pathogenic filariae, requiring the use of surrogate parasites for Onchocerca volvulus for both ex vivo and in vivo evaluation. Herein, we describe a platform utilizing phenotypic ex vivo assays consisting of the free-living nematode Caenorhabditis elegans, microfilariae and adult filariae of the bovine filariae Onchocerca lienalis and Onchocerca gutturosa, respectively, as well as microfilariae and adult filariae of the feline filariae Brugia pahangi, the rodent filariae Litomosoides sigmodontis and the human-pathogenic filariae Brugia malayi to assess activity across various surrogate parasites. Utilization of those surrogate nematodes for phenotypic ex vivo assays in order to assess activity across various parasites led to the successful establishment of a screening cascade and identification of multiple compounds with potential macrofilaricidal activity and desirable physicochemical, MW = 200–400 and low lipophilicity, logP <4, and pharmacokinetic properties, rat and human liver S9 stability of ≥70% remaining at 60 min, and AUC exposures above 3 μM h. This platform demonstrated the successful establishment of a screening cascade which resulted in the discovery of potential novel macrofilaricidal compounds for futher drug discovery lead optimization efforts. This screening cascade identified two distinct chemical series wherein one compound produced a significant 68% reduction of adult Litomosoides sigmodontis in the mouse model. Successful demonstration of efficacy prompted lead optimization medicinal chemistry efforts for this novel series. Graphical abstract: Image 1 Highlights: Successful establishment of a screening cascade for filaricidal drug discovery. Chemical series with promising physiochemical and pharmacokinetic properties. Identification of a hit compound with macrofilaricidal efficacy.